Magadacerina, a new genus of Leptoceridae (Trichoptera) from Madagascar - Malm, Tobias; Johanson, Kjell Arne (Zootaxa, 2013)
Magadacerina forcipata, new genus, new species (Trichoptera: Leptoceridae), is described from Madagascar. The monotypic genus is characterised by having the tibial spur formula 2,2,2; wings with sessile bifurcation of M; genitalia with preanal appendages fused with segment IX and greatly produced posterad, and a tergum X with an anteriorly extended ventral base articulating with a sclerotised spine-like process of the phallic shield. The new genus is most closely related to Blyzophilus in the tribe Blyzophilini.